2020
DOI: 10.1177/0361198120919404
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Long-Term Durability of Lime Treatment in Hydraulic Structures: Case Study on the Friant-Kern Canal

Abstract: The slopes along the Friant-Kern Canal were last treated in the 1970s with 4% quick lime to mitigate issues related to slope failure caused by expansive Porterville soils. The immediate benefits of lime treatment were well documented by the Bureau of Reclamation. However, questions remain over the long-term durability of lime-treated materials. In this study, we compare the engineering properties and changes in the soil mineralogy of treated and untreated sections to establish the effectiveness of lime after m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Mechanical improvement involves the use of proper implementation techniques such as proper mixing of soil with chemical binder and water, compaction of soil through a suitable mechanism, and at an appropriate water content and compaction energy (le Runigo et al, 2011(le Runigo et al, , 2009Little, 1987). Chemical stabilization consists of the use of inorganic or organic binders, such as slags (Poh et al, 2006;Wild et al, 1998), fly ashes produced from coal-burning (Kolias et al, 2005;Show et al, 2003), cement kiln dust (Miller and Azad, 2000), and lime (Akula et al, 2020;Ali and Mohamed, 2019;Das et al, 2020;2021;Makki-Szymkiewicz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical improvement involves the use of proper implementation techniques such as proper mixing of soil with chemical binder and water, compaction of soil through a suitable mechanism, and at an appropriate water content and compaction energy (le Runigo et al, 2011(le Runigo et al, , 2009Little, 1987). Chemical stabilization consists of the use of inorganic or organic binders, such as slags (Poh et al, 2006;Wild et al, 1998), fly ashes produced from coal-burning (Kolias et al, 2005;Show et al, 2003), cement kiln dust (Miller and Azad, 2000), and lime (Akula et al, 2020;Ali and Mohamed, 2019;Das et al, 2020;2021;Makki-Szymkiewicz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical stabilization involves the execution process, such as the soil-binder mixing process, 42 using an appropriate binder and water contents during compaction and mixing, implementing the accurate 43 compaction conditions [6,[14][15]. 44 So far, few field investigations have reported the sustainability of earth structures attained through 45 such improvements [5,8,[16][17][18][19]. Akula et al [16] studied the performance of the Friant-Kern Canal in 46 California, the United States, which was built with 4% quicklime treated plastic soil after 40 years from 47 treatment.…”
Section: Introduction 34mentioning
confidence: 99%
“…44 So far, few field investigations have reported the sustainability of earth structures attained through 45 such improvements [5,8,[16][17][18][19]. Akula et al [16] studied the performance of the Friant-Kern Canal in 46 California, the United States, which was built with 4% quicklime treated plastic soil after 40 years from 47 treatment. Based on the investigations, they have reported increased long-term strength, reduction in 4 lime-treated soil to extreme wetting and drying cycles accompanied by a wetting fluid of different chemical 76 nature might impact the soil pH and can modify the long-term performance.…”
Section: Introduction 34mentioning
confidence: 99%
“…They showed that the lime-treated coir geotextile reduced the upward swell pressure by approximately 52% to 81%, resulting in a thinner subbase and base course layer in the pavement design. The long-term durability of the lime-treated material, after more than 40 years of performance, was shown in a study by Akula et al (7). In an early study by Neubauer and Thompson (8), the strength and deformation properties (California Bearing Ratio [CBR], shear strength and moduli of deformation) of uncured lime-soil mixtures compacted on the wet side of optimum were substantially better than those of untreated natural soils.…”
mentioning
confidence: 97%